2020
DOI: 10.1136/neurintsurg-2020-016513
|View full text |Cite
|
Sign up to set email alerts
|

The professional and personal impact of the coronavirus pandemic on US neurointerventional practices: a nationwide survey

Abstract: BackgroundLittle is currently known about the effects of the coronavirus (COVID-19) pandemic on neurointerventional (NI) procedural volumes or its toll on physician wellness.MethodsA 37-question online survey was designed and distributed to physician members of three NI physician organizations.ResultsA total of 151 individual survey responses were obtained. Reduced mechanical thrombectomy procedures compared with pre-pandemic were observed with 32% reporting a greater than 50% reduction in thrombectomy volumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The most common psychological symptoms measured with surveys or validated questionnaires reported included anxiety (n = 103), depression (n = 73), stress (n = 68), fear (n = 61), burnout (n = 25), mental distress/health (n = 21), and post-traumatic stress disorder (PTSD) (n = 14) (Additional File 3). Most COVID-19 studies reported on physicians from USA (n = 23) [41,52,66,70,77,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107], China (n = 22) [15, 49, 54-56, 65, 68, 73, 86, 89, 102, 108-118] followed by India (n = 21) [40,50,58,63,67,71,102,[119][120][121][122][123][124][125][126][127][128][129][130][131][132] [41,52,…”
Section: Experiences With Physician Psychological Symptoms During Infectious Disease Outbreaksmentioning
confidence: 99%
“…The most common psychological symptoms measured with surveys or validated questionnaires reported included anxiety (n = 103), depression (n = 73), stress (n = 68), fear (n = 61), burnout (n = 25), mental distress/health (n = 21), and post-traumatic stress disorder (PTSD) (n = 14) (Additional File 3). Most COVID-19 studies reported on physicians from USA (n = 23) [41,52,66,70,77,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107], China (n = 22) [15, 49, 54-56, 65, 68, 73, 86, 89, 102, 108-118] followed by India (n = 21) [40,50,58,63,67,71,102,[119][120][121][122][123][124][125][126][127][128][129][130][131][132] [41,52,…”
Section: Experiences With Physician Psychological Symptoms During Infectious Disease Outbreaksmentioning
confidence: 99%
“…The novel Coronavirus Disease 2019 (COVID-19) pandemic has changed the way we live and practice modern day medicine. 1 In an effort to practice physical distancing, many specialties have moved routine patient encounters to telephone and virtual platforms. [2][3][4] These changes may not be temporary.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine approaches have helped to mitigate adverse effects of this by replacing or augmenting some previous routine clinical activities. [6][7][8][9] Given the persistence of worldwide travel restrictions, teleproctoring for the introduction and supervision of the safe use of novel devices is becoming necessary.…”
Section: Discussionmentioning
confidence: 99%